Reliability of Ultrasonography in Measuring Thickness of Flexor and Extensor Muscles in Healthy Subjects and Patients with Cervical Vertigo - Zargar Talebi, Ronak; Rezasoltani , Asghar; Khalkhalizavieh , Minoo; Dehghan Manshadi , Farideh; Akbarzadeh Baghban , Alireza (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Vertigo is the third most common complaint among all outpatients worldwide. The cervical region impairment is one of the peripheral causes of the vertigo. Rehabilitative Ultrasound imaging (RUSI) has been introduced, as a non-invasive method to measure the muscle thickness. The purpose of this study was to assess the intra-rater reliability of musculoskeletal ultrasound (MSKUS), as a tool for measuring cervical flexor and extensor muscles thicknesses in the healthy subjects and the patients with cervical vertigo. Material and Methods: in this study, 44 subjects were assessed in similar sitting position and procedure. Examiner measured the cervical flexor and extensor muscles thicknesses, in two separate days, by the same musculoskeletal ultrasound specialists' raters. Data analysis and assessment of reliability were performed using the Intra-class Correlation Coefficient (ICC), Standard Error of Measurement (SEM), and the Smallest Detectable Difference (SDD). Results: Results reflected the excellent intra-rater reliability of ultrasonography to measure the cervical flexor and extensor muscles thicknesses in the healthy participants and the patients with cervical vertigo. Conclusion: The results of the current study indicate that, MSKUS is a reliable tool for measuring the cervical flexor and extensor muscles thicknesses in healthy subjects and the patients with cervical vertigo. Keywords: Cervical Spine, Muscle, Ultrasonography